A weekend with Rousseau - Plazy, Gilles, 1942- (New York : Rizzoli, 1993)
The ninteenth-century French painter who captured the sights of Paris talks about his life and work as if entertaining the reader for the weekend. Includes reproductions of the artist's work and a list of museums where they are on display.
Keywords: Rousseau, Henri Julien Felix, -- 1844-1910.e literature; Painters -- France -- Biography -- Juvenile literature; Artists